Investigating the Paracrine Role of Perinatal Derivatives: Human Amniotic Fluid Stem Cell-Extracellular Vesicles Show Promising Transient Potential for Cardiomyocyte Renewal - Costa, Ambra; Balbi, Carolina; Garbati, Patrizia; Palamà, Maria Elisabetta Federica; Reverberi, Daniele; De Palma, Antonella; Rossi, Rossana; Paladini, Dario; Coviello, Domenico; De Biasio, Pierangela; Ceresa, Davide; Malatesta, Paolo; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Cardiomyocyte renewal represents an unmet clinical need for cardiac regeneration. Stem cell paracrine therapy has attracted increasing attention to resurge rescue mechanisms within the heart. We previously characterized the paracrine effects that human amniotic fluid-derived stem cells (hAFSC) can exert to provide cardioprotection and enhance cardiac repair in preclinical models of myocardial ischemia and cardiotoxicity. Here we analyse whether hAFSC secretome formulations, namely hAFSC-conditioned medium (hAFSC-CM) over extracellular vesicles (hAFSC-EVs) separated from it, can induce cardiomyocyte renewal. c-KIT+ hAFSC were obtained by leftover samples of II trimester prenatal amniocentesis (fetal hAFSC) and from clinical waste III trimester amniotic fluid during scheduled C-section procedures (perinatal hAFSC). hAFSC were primed under 1% O2 to enrich hAFSC-CM and EVs with cardioactive factors. Neonatal mouse ventricular cardiomyocytes (mNVCM) were isolated from cardiac tissue of R26pFUCCI2 mice with cell-cycle fluorescent tagging by mutually exclusive nuclear signal. mNVCM were stimulated by fetal versus perinatal hAFSC-CM and hAFSC-EVs to identify the most promising formulation for in vivo assessment in a R26pFUCCI2 neonatal mouse model of myocardial infarction (MI) via intra-peritoneal delivery. While the perinatal hAFSC secretome did not provide any significant cardiogenic effect, fetal hAFSC-EVs significantly sustained mNVCM transition from S- to M-phase by 2-fold, while triggering cytokinesis by 4.5-fold over vehicle-treated cells. Treated mNVCM showed disorganized expression of cardiac alpha-actinin, suggesting cytoskeletal re-arrangements prior to cell renewal, with a 40% significant down-regulation of Cofilin-2 and a positive trend of polymerized F-Actin. Fetal hAFSC-EVs increased cardiomyocyte cell cycle progression by 1.8-fold in the 4-day-old neonatal left ventricle myocardium short term after MI; however, such effect was lost at later stage. Fetal hAFSC-EVs were enriched with a short isoform of Agrin, a mediator of neonatal heart regeneration acting by YAP-related signaling; yet, in vitro application of YAP-inhibitor Verteporfin partially affected EV paracrine stimulation on mNVCM. EVs secreted by developmentally juvenile fetal hAFSC can support cardiomyocyte renewal to some extension, via intercellular conveyance of candidates possibly involving Agrin in combination with other factors. These perinatal derivative promising cardiogenic effects need further investigation to define their specific mechanism of action and enhance their potential translation into therapeutic opportunity.